Mental health self-assessment system in the pandemic in Colombia - Augusto Pérez-Gómez; Alejandra Villamil-Sánchez; Orlando Scoppetta DG (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2021)
Background: The COVID-19 pandemic has brought different impacts on human life unfortunately, mental health  has not received  due attention.  Methods: The Nuevos Rumbos Corporation (CNR) decided to create a self- assessment system that allows measuring the impact that confinement has had in different areas of adjustment in life of Colombians.  Findings: More than 2000 people have used the system, (74.2% women, 24.2% men and 1.6% qualify as "other"), about 62% of the respondents report negative emotional changes, 33% have felt more aggressive than usual, 12% reported an increase in alcohol consumption and of active smokers 32.5% increased their consumption. Interpretation: As a result of the limitations associated with the pandemic, there is evidence of a global imbalance in the mental health of the population that requires attention, since the problems will increase as the economic problems continue as well as the confinement, associated with a second wave of the virus. Funding: We declare that we have no conflict of interest in the preparation or publication of this paper, Nuevos Rumbos being completely autonomous in the application of the system as well as in the administration of its data.